Comparative study on the thermal degradation of dry- and wet-torrefied woods. (1st January 2017) - Bach, Quang-Vu; Tran, Khanh-Quang; Skreiberg, Øyvind
Highlights: Dry and wet torrefaction affect differently on the pyrolysis and combustion kinetics of Norway spruce stem wood. Degradation peaks of dry-torrefied wood are located at lower temperatures than those for wet-torrefied woods. Dry-torrefied wood shows a significantly higher combustion peak than wet-torrefied woods. Dry torrefaction does not influence the activation energy of wood cellulose and lignin, but wet torrefaction does. Dry and wet torrefaction have different effects on the kinetic parameters of char. Abstract: In this study, effects of dry and wet torrefaction on the pyrolysis and combustion kinetics of Norway spruce stem wood were directly compared. The dry- and wet-torrefied woods were produced at appropriate conditions on the basis of a similar mass yield. Thermal reactivity of the woods was thermogravimetrically studied in nitrogen and air to simulate pyrolysis and combustion conditions, followed by a kinetic evaluation employing multi-pseudo-component models. The results show that the woods devolatilize more actively in air than in nitrogen. Moreover, the devolatilization and combustion peaks of the dry-torrefied wood are always located at lower temperatures than those for the wet-torrefied woods. Also, the dry-torrefied wood shows a significantly higher combustion peak than the wet-torrefied woods, but it ends at a lower temperature. Dry torrefaction removes more hemicellulose from the wood than wet torrefaction, at comparable conditions. It appears that dry torrefaction has unpronounced effects on the activation energy of cellulose and lignin in the subsequent thermal conversion processes, while these figures increase after wet torrefaction. In addition, wet and dry torrefaction show opposite trends in the char combustion: while dry torrefaction increases both the activation energy and pre-exponential factor of char, wet torrefaction decreases these kinetic parameters. Nevertheless, the mass fraction of char for the wet-torrefied woods is slightly higher than that for the dry-torrefied wood.